COMPUTER AIDED DRUG DESIGN OF PDE 4 INHIBITORS FOR POTENTIAL THERAPY AGAINST CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) - Miss. Pragati Vastri, Dr. Arun Patel, Mr. Shailendra Patel, Mr. Vijay Pratap Ahirwar, (EPRA International Journal of Research and Development (IJRD), 2023)
Chronic Obstructive Pulmonary Disease (COPD) is an inflammatory disease. it is collection of lung diseases including chronic bronchitis, emphysema and chronic obstructive airways disease. COPD is characterized by persistent airflow limitation that is usually progressive and is associated with an enhanced chronic inflammatory response in the airways and lungs to noxious particles and gases. In the inflammatory cells cAMP plays the role of a negative regulator of the primary activating pathways such as cytokine release by T-cells. Levels of cAMP on the other hand are regulated by cAMP-specific PDE isozymes (e.g., PDE4 predominantly expressed in inflammatory and immune cells in addition to brain). Inhibition of the PDE4 in these cells effectively elevates the intracellular cAMP levels, thereby activating specific protein phosphorylation cascades that elicit a variety of functional responses. Additionally, elevation of intracellular cAMP levels via inhibition of PDE4 activity led to smooth muscle relaxation and thereby bronchodilation that is beneficial for the management of respiratory diseases like COPD.